Difference between revisions of "1967 AHSME Problems/Problem 23"

(Created page with "== Problem == If <math>x</math> is real and positive and grows beyond all bounds, then <math>\log_3{(6x-5)}-\log_3{(2x+1)}</math> approaches: <math>\textbf{(A)}\ 0\qquad \textbf...")
 
 
Line 9: Line 9:
  
 
== Solution ==
 
== Solution ==
<math>\fbox{B}</math>
+
Since <math>\log_b x - \log_b y = \log_b \frac{x}{y}</math>, the expression is equal to <math>\log_3 \frac{6x - 5}{2x + 1}</math>.
 +
 
 +
The expression <math>\frac{6x - 5}{2x + 1}</math> is equal to <math>3 - \frac{8}{2x + 1}</math>.  As <math>x</math> gets large, the second term approaches <math>0</math>, and thus <math>\frac{6x - 5}{2x + 1}</math> approaches <math>3</math>.  Thus, the expression approaches <math>\log_3 3</math>, which is <math>1</math>.
 +
 
 +
Alternately, we divide the numerator and denominator of <math>\frac{6x - 5}{2x + 1}</math> by <math>x</math> to get <math>\frac{6 - \frac{5}{x}}{2 + \frac{1}{x}}</math>.  As <math>x</math> grows large, both fractions approach <math>0</math>, leaving <math>\frac{6}{2} = 3</math>, and so the expression approaches <math>\log_3 3 = 1</math>.
 +
 
 +
With either reasoning, the answer is <math>\fbox{B}</math>
  
 
== See also ==
 
== See also ==

Latest revision as of 23:48, 12 July 2019

Problem

If $x$ is real and positive and grows beyond all bounds, then $\log_3{(6x-5)}-\log_3{(2x+1)}$ approaches:

$\textbf{(A)}\ 0\qquad \textbf{(B)}\ 1\qquad \textbf{(C)}\ 3\qquad \textbf{(D)}\ 4\qquad \textbf{(E)}\ \text{no finite number}$

Solution

Since $\log_b x - \log_b y = \log_b \frac{x}{y}$, the expression is equal to $\log_3 \frac{6x - 5}{2x + 1}$.

The expression $\frac{6x - 5}{2x + 1}$ is equal to $3 - \frac{8}{2x + 1}$. As $x$ gets large, the second term approaches $0$, and thus $\frac{6x - 5}{2x + 1}$ approaches $3$. Thus, the expression approaches $\log_3 3$, which is $1$.

Alternately, we divide the numerator and denominator of $\frac{6x - 5}{2x + 1}$ by $x$ to get $\frac{6 - \frac{5}{x}}{2 + \frac{1}{x}}$. As $x$ grows large, both fractions approach $0$, leaving $\frac{6}{2} = 3$, and so the expression approaches $\log_3 3 = 1$.

With either reasoning, the answer is $\fbox{B}$

See also

1967 AHSME (ProblemsAnswer KeyResources)
Preceded by
Problem 22
Followed by
Problem 24
1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30
All AHSME Problems and Solutions

The problems on this page are copyrighted by the Mathematical Association of America's American Mathematics Competitions. AMC logo.png

Invalid username
Login to AoPS